Foresight as a tool for implementing the directions of new industrialization - O. V. Myasnyankina; A. A. Zaitsev (Вестник университета, 2023)
The subject of the study is the process of reindustrialization in the old industrial region, where the main development resources are preserved, but the activity level of innovative processes is insufficient.The purpose of the study is the possibility of applying foresight methods in the implementation of neoindustrialization projects in the region.The methodology includes a monographic study of the industrialization processes dynamics, a comparative analysis of procedures for changing the structure of industrial production, and a foresight conducting methodology.The main result of the study is the substantiation of the choice of the most effective method of applying foresight, as well as the construction of a reindustrialization roadmap on the example of the Voronezh region. The application of these results is possible in other territorial entities (region, municipal unit) involved in the implementation of foresight projects for the development of industry.Prospects: research development - creation of a model methodology for the use of foresights in the implementation of large-scale complex projects at the regional level.Conclusions: the use of foresight in determining the prospects for the revival of the high-tech industry will help to increase the efficiency of decisions to attract resources to the development of priority benchmark, industrial production.